Small cell carcinoma of the thymus associated with cerebellar dysfunction - Peppes, V.I.; Dimopoulos, S.K.; Anagnostopoulos, A.; Dimopoulos, M.A.; Anastasiou-Nana, M.I. (American Journal of Case Reports, 2008)
Background: Small cell carcinomas (SCC) originate mainly from bronchial tissue. Several extrapulmonary sites of origin have been described, including the genitourinary and gastrointestinal tracts, the ear, nose and throat and lymph nodes. SCC of the lung may be associated with paraneoplastic neurologic syndromes. Case Report: We report an oat cell histological variant of SCC found in the thymus gland of a 53-year-old woman who presented with subacute cerebellar dysfunction. Conclusions: SCC of the thymus gland, which is a rare extrapulmonary site of origin of SCC, accompanied by cerebellar dysfunction, is rarely reported.
Keywords: Cerebellar dysfunction; Mediastinal tumour; Oat cell carcinoma; Paraneoplastic syndrome